Detection of tick-borne infection in Morgellons disease patients by serological and molecular techniques - Middelveen MJ; Du Cruz I; Fesler MC; Stricker RB; Shah JS (Dove Medical Press, 2018)
Marianne J Middelveen,1 Iris Du Cruz,2 Melissa C Fesler,3 Raphael B Stricker,3 Jyotsna S Shah2 1Atkins Veterinary Services, Calgary, AB, Canada; 2IGeneX Laboratories, Palo Alto, CA, USA; 3Union Square Medical Associates, San Francisco, CA, USA Background: Morgellons disease (MD) is a skin condition associated with Lyme disease (LD) and tick-borne illness. Patients with this skin disorder experience ulcerative lesions that contain multicolored filamentous collagen and keratin inclusions. Infection with various species of Borrelia and other tick-borne pathogens has been detected in tissue and body fluid specimens from MD patients. We sought to explore this association further in a cohort of MD patients.Patients and methods: Sera from 30 patients with MD were tested for antibody reactivity to antigens from the Borrelia burgdorferi (Bb) group and the relapsing fever Borrelia (RFB) group of spirochetes. Tissue and/or body fluid specimens from these patients were also tested for the presence of Bb and RFB infection using PCR technology. In addition, tissue and body fluid specimens were tested for the presence of Bartonella henselae using PCR, and formalin-fixed skin sections from a subset of patients were tested using fluorescent in situ hybridization (FISH) with B. henselae-specific DNA probes.Results: Seroreactivity to Bb, RFB or both was detected in 63% of the cohort, while positive PCR testing for Bb, RFB or both was detected in 53% of the cohort. Overall, 90% of patients tested positive for exposure and/or infection with Borrelia spirochetes. B. henselae infection was detected by PCR in skin sections or body fluids from 20% of the subjects, and B. henselae FISH testing was positive in 30% of the dermatological specimens submitted for study.Conclusion: The study demonstrates an association between MD and positive tests for both Bb and RFB spirochetes. In conjunction with previous studies, our study provides corroborative evidence linking MD to Borrelia infection and tick-borne illness. Keywords: Lyme disease, Borrelia burgdorferi, Morgellons disease, relapsing fever Borrelia, Bartonella, tick-borne disease